Prospects of mestizaje and pluricultural democracy: the Venezuelan Case of an imagined and a real Venezuelan society - Pérez, Berta E.; Perozo, Abel A. (Anuário Antropológico, 2018)
This essay is a historic-political analysis of mestizaje from which a new interpretation is proposed. Such new perspective is aimed at examining the biological and/or cultural mixing among different cultural segments or individuals for “what it is,” rather than to continue viewing it from “what it has become.” From this latter aspect, mestizaje is “(...) an elite-generated myth of national identity (...) [that] tends to obscure the conditions of its own creation, to cover its own tracks” (Hale 1996: 2). But once unmasked, it is an ideological instrument of power fabricated by and utilized among the elite for the preservation of its own socio-economic and political interests.